2022
DOI: 10.1101/2022.06.19.496730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demographic history and genetic structure in pre-Hispanic Central Mexico

Abstract: Aridoamerica and Mesoamerica are two distinct cultural areas that hosted numerous pre-Hispanic civilizations between 2,500 BCE and 1,521 CE. The division between these regions shifted southward due to severe droughts ca. 1,100 years ago, allegedly driving demographic changes and population replacement in some sites in central Mexico. Here, we present shotgun genome-wide data from 12 individuals and 26 mitochondrial genomes from eight pre-Hispanic archaeological sites across Mexico, including two at the shiftin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Hot, wet and acid environments adversely affect the quality of aDNA preservation (Roca-Rada et al, 2020). Nevertheless, studies such as the ones cited above, as well as our own, demonstrate that the acquisition of aDNA in such conditions is not only possible but recommended (Llamas and Roca-Rada, 2023;Villa-Islas et al, 2023), as it opens up fresh perspectives over an entire field of ancient Maya archaeology.…”
Section: Discussionmentioning
confidence: 79%
“…Hot, wet and acid environments adversely affect the quality of aDNA preservation (Roca-Rada et al, 2020). Nevertheless, studies such as the ones cited above, as well as our own, demonstrate that the acquisition of aDNA in such conditions is not only possible but recommended (Llamas and Roca-Rada, 2023;Villa-Islas et al, 2023), as it opens up fresh perspectives over an entire field of ancient Maya archaeology.…”
Section: Discussionmentioning
confidence: 79%
“…We evaluated different topologies based on the worst Z-score and the presence of zero-length internal branches, as well as incorporating information from our analyses about the relationship between these populations. For example, we were able to replicate the gene flow from an unsampled population (UPopA) into Mixe [3,5]. Within South America, we included representatives of the north coast of Peru (Eten), central-south Peru (Paran), and central-south Chile (Mapuche-Huilliche).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we emphasize the branching pattern (TreeMix and qpGraph) and split times (momi2) within our demographic analyses, rather than recent population sizes, although the elevated genetic drift within the Americas relative to populations from other geographic Still, when considering populations that have experienced significant degrees of genetic drift, it is important to consider the results of PCA in light of other results as we have here, because PCs are related to measures of inter-population genetic drift (24). The finding of a previously unidentified lineage in the Americas that emerged in the Late Pleistocene builds on a pattern of multiple lineages being identified before the split of the Northern and Southern Native American lineages including the Ancient Beringian lineage (2), the population represented by the lineage associated with the Big Bar ancestor (3), and "ghost" populations contributing to the genomic diversity in the Americas most recently identified through statistical analyses (5,6). These findings are potentially consistent with models of multiple populations radiating from a single source into vast geographic lands, evolving in relative isolation into different lineages early on, before interacting with nearby communities later in time as we infer here with the Blood/Blackfoot.…”
Section: Discussionmentioning
confidence: 98%
“…However, the ancient lineages identified in these studies have not been observed in samples of Indigenous peoples of the Americas living today. Research in Mesoamerica and South America suggests that certain sampled populations (e.g., Mixe) have at least partial ancestry in present-day Indigenous groups from unknown genomic lineages in the Americas, possibly dating as far back as 25,000 years ago (3,5,6).…”
Section: Introductionmentioning
confidence: 99%